Vertical tumor-positive resection margins and the risk of residual neoplasia after endoscopic resection of Barrett’s neoplasia: a nationwide cohort with pathology reassessment - van Tilburg, Laurelle; Verheij, Eva P. D.; van de Ven, Steffi E. M.; van Munster, Sanne N.; Weusten, Bas L. A. M.; Herrero, Lorenza Alvarez; Nagengast, Wouter B.; Schoon, Erik J.; Alkhalaf, Alaa; Bergman, Jacques J. G. H. M.; Pouw, Roos E.; Oudijk, Lindsey; Meijer, Sybren L.; Jansen, Marnix; Doukas, Michail; Koch, Arjun D.; on behalf of the Dutch Barrett Expert Centers and the Dutch Barrett Expert Centers Study Group; Brosens, Lodewijk A. A.; Curvers, Wouter L.; Houben, Martin H. M. G.; de Jonge, Pieter Jan F.; Kats-Ugurlu, Gursah; van der Laan, Jaap S.; van Lijnschoten, Ineke G.; Moll, Freek C. P.; Ooms, Ariadne H. A. G.; Raicu, G. Mihaela; Tang, Thjon J.; Westerhof, Jessie (Endoscopy, 2024)
Background This study evaluated the proportion of patients with residual neoplasia after endoscopic resection (ER) for Barrett’s neoplasia with confirmed tumor-positive vertical resection margin (R1v).Methods This retrospective cohort study included patients undergoing ER for Barrett’s neoplasia with histologically documented R1v since 2008 in the Dutch Barrett Expert Centers. We defined R1v as cancer cells touching vertical resection margins and Rx as nonassessable margins. Reassessment of R1v specimens was performed by experienced pathologists until consensus was reached regarding vertical margins.Results 101/110 included patients had macroscopically complete resections (17 T1a, 84 T1b), and 99/101 (98%) ER specimens were histologically reassessed, with R1v confirmed in 74 patients (75%), Rx in 16%, and R0 in 9%. Presence/absence of residual neoplasia could be assessed in 66/74 patients during endoscopic reassessment (52) and/or in the surgical resection specimen (14), and 33/66 (50%) had residual neoplasia. Residual neoplasia detected during endoscopy was always endoscopically visible and biopsies from a normal-appearing ER scar did not detect additional neoplasia. Of 25 patients who underwent endoscopic follow-up (median 37 months [interquartile range 12–50]), 4 developed local recurrence (16.0%), all detected as visible abnormalities. Conclusions After ER with R1v, 50% of patients had no residual neoplasia. Histological evaluation of ER margins appears challenging, as in this study 75% of documented R1v cases were confirmed during reassessment. Endoscopic reassessment 8–12 weeks after ER seems to accurately detect residual neoplasia and can help to determine the most appropriate strategy for patients with R1v.